2015
DOI: 10.2310/8000.2013.131349
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes of bloodstream infections in patients discharged from the emergency department

Abstract: Objective: To determine the outcomes of patients discharged from the emergency department (ED) with a bloodstream infection (BSI) and how these outcomes are influenced by antibiotic treatment. Methods: We identified every BSI in adult patients discharged from our ED to the community between July 1, 2002, and March 31, 2011. The medical records of all cases were reviewed to determine antibiotic treatment in the ED and at discharge. Microorganism sensitivities were used to determine whether antibiotics were appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The present study found that overall mortality in patients with a BSI following ER discharge was low (3.9%) and no different from that in patients with a BSI who were admitted immediately. This finding is consistent with that of previous studies demonstrating that the mortality rate in patients with a BSI who were discharged from the ER ranged from 0% to 5.0% [ 5 , 9 , 11 , 17 , 18 , 20 ]. However, our study also found that a higher proportion of patients discharged with no antimicrobial therapy (ie, no antimicrobials were given at the ER visit or were prescribed on discharge) returned to the ER with sepsis or died within 28 days.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study found that overall mortality in patients with a BSI following ER discharge was low (3.9%) and no different from that in patients with a BSI who were admitted immediately. This finding is consistent with that of previous studies demonstrating that the mortality rate in patients with a BSI who were discharged from the ER ranged from 0% to 5.0% [ 5 , 9 , 11 , 17 , 18 , 20 ]. However, our study also found that a higher proportion of patients discharged with no antimicrobial therapy (ie, no antimicrobials were given at the ER visit or were prescribed on discharge) returned to the ER with sepsis or died within 28 days.…”
Section: Discussionsupporting
confidence: 93%
“…This finding raises the question of the potential value of routine antimicrobial therapy in patients discharged after a blood culture collection. Nevertheless, previous studies noted that patients with a BSI after ER discharge were less likely to receive appropriate antimicrobial therapy than those with a BSI who were admitted immediately [ 10 , 11 ], and that inappropriate antimicrobial therapy was associated with a high mortality rate or urgent readmission [ 5 , 9 ]. Moreover, antimicrobial therapy without appropriate diagnosis may counteract antimicrobial stewardship in the ER [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, its isolation rate ranked first for many years, and it was an extensively drug-resistant strain. Acinetobacter baumannii in the emergency department is mostly due to nosocomial infection during hospitalization[13,14], and there are few reports that Acinetobacter baumannii causes community infection.…”
Section: Discussionmentioning
confidence: 99%
“…ED patients with undiagnosed bacteremia who are discharged have a higher rate of unplanned hospitalization or readmission to the ED. 3 Prompt recognition of bacteremia and appropriate treatment are essential to ensure positive patient outcomes.…”
Section: Introductionmentioning
confidence: 99%